Perioperative management of patients with pulmonary hypertension undergoing non-cardiothoracic, non-obstetric surgery: a systematic review and expert consensus statement. (April 2021) - Price, Laura C.; Martinez, Guillermo; Brame, Aimee; Pickworth, Thomas; Samaranayake, Chinthaka; Alexander, David; Garfield, Benjamin; Aw, Tuan-Chen; McCabe, Colm; Mukherjee, Bhashkar; Harries, Carl; Kempny, Aleksander; et al.
Abstract: Background: The risk of complications, including death, is substantially increased in patients with pulmonary hypertension (PH) undergoing anaesthesia for surgical procedures, especially in those with pulmonary arterial hypertension (PAH) and chronic thromboembolic PH (CTEPH). Sedation also poses a risk to patients with PH. Physiological changes including tachycardia, hypotension, fluid shifts, and an increase in pulmonary vascular resistance (PH crisis) can precipitate acute right ventricular decompensation and death. Methods: A systematic literature review was performed of studies in patients with PH undergoing non-cardiac and non-obstetric surgery. The management of patients with PH requiring sedation for endoscopy was also reviewed. Using a framework of relevant clinical questions, we review the available evidence guiding operative risk, risk assessment, preoperative optimisation, and perioperative management, and identifying areas for future research. Results: Reported 30 day mortality after non-cardiac and non-obstetric surgery ranges between 2% and 18% in patients with PH undergoing elective procedures, and increases to 15–50% for emergency surgery, with complications and death usually relating to acute right ventricular failure. Risk factors for mortality include procedure-specific and patient-related factors, especially markers of PH severity (e.g. pulmonary haemodynamics, poor exercise performance, and right ventricular dysfunction). Most studies highlight the importance of individualised preoperative risk assessment and optimisation and advanced perioperative planning. Conclusions: With an increasing number of patients requiring surgery in specialist and non-specialist PH centres, a systematic, evidence-based, multidisciplinary approach is required to minimise complications. Adequate risk stratification and a tailored-individualised perioperative plan is paramount.